Pengukuran level pembentukan es (ICING) pada pemodelan menggunakan rancang bangun sensor berbasis perubahan frekuensi dengan induktor datar - Yoga Dwi Cahyono; Samsul Hidayat; Nugroho Adi Pramono (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
Icing is one of the main dangers for the flight and are cumulative. The icing is a process of accumulation of ice on parts of the aircraft, which will lead to changes in geometry and resulted in a variety of other disorders. For example, there was a buildup of ice on the propellor (propeller) and the engine carburetor so it can reduce the thrust plane even caused the plane to fall freely (stall). For it needs to be designed and built the Icing Detector as well as the actuator in providing early warning of the existence of the calculation and the icing on the pilot. This instrument is designed with electronic units that use the oscillator as frequency generator and frequency meter based mikrokontroller ATmega8 as the measuring frequency. The surface of the sensor is made up of printed inductor with a broad surface for detection area. Sensors and electronic units connected by cable. In addition, modeling for the pilot indicators have been designed using the LCD. Research results suggest that testing on "Ice Accretion-Level Measurement On Modelling using printed Inductor Sensor Prototype Based On Frequency Shifting" has been a successful made in accordance with the expected functions. These instruments can detect the occurrence of icing and give an indication of the thickness of the ice. It is possible to form a flat sensor installation on the aircraft to be more unobtrusive air flow, as well as a spacious surface produces more accurate results.